If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8 ( x - 9 ) = 3 ( x - 4 )
We simplify the equation to the form, which is simple to understand
8(x-9)=3(x-4)
Reorder the terms in parentheses
+(+8x-72)=3*(x-4)
Remove unnecessary parentheses
+8x-72=+3+*(+x-4+)
Reorder the terms in parentheses
+8x-72=+(+3x-12)
Remove unnecessary parentheses
+8x-72=+3x-12
We move all terms containing x to the left and all other terms to the right.
+8x-3x=-12+72
We simplify left and right side of the equation.
+5x=+60
We divide both sides of the equation by 5 to get x.
x=12
| 16-2x=19-4x | | 9d=72 | | f(x)=2x^2+9x-1 | | 9/x+3=0 | | f(x)=81 | | 7x/y=41 | | 16r=0.8Y | | 7a+2a+3b+3b= | | X=0.8Y-16r | | 5/7y+2/7=4 | | X+2=-x-7 | | (16x^2-8)=81 | | 13x=-12+10x | | d+2.7t=-4.8t-6 | | 5v^2=35v | | 4x+8x=9-5x | | x^3-21x^2+33x-243=0 | | 7-20=6x-5-5x | | [m+4]+4=14 | | 12=3x-16 | | y^2-12y+36=100 | | 8+10x+2x=3+12x | | [m+4]+6=24 | | 5t+11=7t-15 | | 4x+8=2(x+6) | | 9y-3=6y+6 | | 147-6x=30x+19 | | 42-4t=12+6t | | -116x-7x=7x+24 | | 3(-4x+8)+3x-4(2x-5)=5x | | 9+2x=6(x+3)-5(x-1) | | 3c=-12 |